Message - Eissa, Mostafa Essam Ahmed (Universal Journal of Pharmaceutical Research, 2018)
It gives me immense pleasure to express my deepest congratulations to all staff and members of Universal Journal of Pharmaceutical Research (UJPR) for their progressive and steady success in scientific publication pathway. One of the prime objectives of UJPR is the continuous development and improvement coupled with motivation and determination to meet the highest academic publication standards. The main emphasis of the journal is to promote scientific papers of good quality and the boundaries were released to cover a broad scope of pharmaceutical studies in different fields. It is felt that there is a huge horizon to explore various fields of scientific research. With clear aims, the editorial board welcomes all researchers and scientists to present their valuable scientific work through the journal. The rapid development in the healthcare sciences has stimulated new ideas and innovations. Accordingly, authors are requested to stick in providing truly genuine high-quality unplagiarized manuscripts that really contribute to the scientific research and will add benefits to mankind. Finally, hearty thanks to all sincere contributors to the success of the journal to cover wide audience interests globally and to disseminate the research internationally which makes the UJPR takes part in contributing to the scientific field effectively.